High angular resolution gravitational wave astronomy - Baker,J; Baker,T; Carbone,C; Congedo,G; Contaldi,C; Dvorkin,I; Gair,J; Haiman,Z; Mota,DF; Renzini,A; Buis,E-J; Cusin,G; et al. (arXiv, 2019)
Since the very beginning of astronomy the location of objects on the sky hasbeen a fundamental observational quantity that has been taken for granted.While precise two dimensional positional information is easy to obtain forobservations in the electromagnetic spectrum, the positional accuracy ofcurrent and near future gravitational wave detectors is limited to between tensand hundreds of square degrees, which makes it extremely challenging toidentify the host galaxies of gravitational wave events or to confidentlydetect any electromagnetic counterparts. Gravitational wave observationsprovide information on source properties and distances that is complementary tothe information in any associated electromagnetic emission and that is veryhard to obtain in any other way. Observing systems with multiple messengersthus has scientific potential much greater than the sum of its parts. Agravitational wave detector with higher angular resolution would significantlyincrease the prospects for finding the hosts of gravitational wave sources andtriggering a multi-messenger follow-up campaign. An observatory with arcminuteprecision or better could be realised within the Voyage 2050 programme bycreating a large baseline interferometer array in space and would havetransformative scientific potential. Precise positional information of standardsirens would enable precision measurements of cosmological parameters and offernew insights on structure formation; a high angular resolution gravitationalwave observatory would allow the detection of a stochastic background andresolution of the anisotropies within it; it would also allow the study ofaccretion processes around black holes; and it would have tremendous potentialfor tests of modified gravity and the discovery of physics beyond the StandardModel.